The Effect of Biological Asset Intensity, Ownership Concentration, Public Ownership, and Audit Committee Meeting on Biological Asset Disclosure - Arsya Noorfitria Putri; Noto Pamungkas; Agung Satmoko (Jurnal Akuntansi Bisnis, 2023)
The existence of biological assets is fully regulated in PSAK 69 which is the adoption of IAS 41. This study aims to provide empirical evidence related to the influence of biological asset intensity, ownership concentration, public ownership, and audit committee meetings on biological asset disclosure. The population used in this study is an agricultural company listed on the Indonesia Stock Exchange (IDX) for the period of 2018 to 2021. The sample selection method used in this study was purposive sampling. Based on the predetermined criteria, a total sample of 15 companies was obtained with a total of 60 firm observations. Data were analyzed using multiple regression analysis methods. Results show that biological assets intensity has a positive influence on the biological assets disclosure of agricultural companies listed on the Indonesia Stock Exchange (IDX) in 2018-2021. However, ownership concentration, public ownership, and audit committee meetings have no effect on the biological assets disclosure of agricultural companies listed on the Indonesia Stock Exchange.